(untitled) (Research, Society and Development, 2021)
Objective: To describe the knowledge and practices adopted by the nursing team to promote the developmental care of preterm newborns assisted in the Neonatal Intensive Care Unit. Methodology: Study with a qualitative approach. The study site took place at the Neonatal Intensive Care Unit of a public hospital in the Federal District-Brazil, in which participated 12 nursing professionals who work at the unit. For data collection, the semi-structured interview and the participants’ characterization form were used. Data analysis was thematic. Results: Three thematic units were identified: Understanding of nursing professionals about developmental care, nursing care in handling the preterm newborn and influence of the environment on the neurodevelopmental evolution of the preterm newborn. Conclusion: We concluded with this study that the NICU nursing team has knowledge about promoting the development of preterm newborns within a neonatal intensive care unit. They are also aware of the negative physiological repercussions that can affect PTNB, in case the implemented nursing care does not follow the philosophy of developmental care.